Pengaruh Senam Hamil terhadap Nyeri Punggung Pada Ibu Hamil di Puskesmas Tiga Juhar Kecamatan STM Hulu Kabupaten Deli Serdang Tahun 2023 - Pinta Br Perangin Angin; Nur Azizah; Khairunisa Khairunisa (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Background Low back pain is a common complaint experienced by pregnant women, with a prevalence reaching 50% in the UK and Scandinavia and 70% in Australia. In Indonesia, the number of pregnant women in 2020 was recorded at 5,298,285 people, with 114,392 of them in North Sumatra. Physiological changes in pregnancy such as uterine enlargement, shifting center of gravity, weight gain, and the influence of the hormone relaxin can cause ligament stretching and muscle spasms that trigger back pain. Although the coverage of antenatal visits (K1 and K4) in North Sumatra has reached the national target, many pregnant women still complain of back pain, mainly due to low participation in prenatal classes. One non-pharmacological intervention proven to be beneficial in reducing back pain is prenatal exercise. This study aimed to determine the effect of prenatal exercise on back pain in pregnant women at the Tiga Juhar Community Health Center, STM Hulu District, Deli Serdang Regency in 2023. Method: This study used a pre-experimental design with a One Group Pre-test and Post-test design without a control group. The study sample consisted of 32 pregnant women who met the inclusion criteria. Back pain intensity data were collected before and after the prenatal exercise intervention, then analyzed using the Wilcoxon Signed Rank Test. Results: Before prenatal exercise, the majority of respondents experienced moderate back pain (53.1%). After the intervention, the majority of respondents experienced mild pain (59.4%). The Wilcoxon test results showed a p-value of 0.002 (<0.05), indicating a significant difference between back pain intensity before and after prenatal exercise.Conclusion: Prenatal exercise has been shown to significantly reduce back pain in pregnant women. Therefore, prenatal exercise can be recommended as an effective non-pharmacological intervention to improve maternal comfort during pregnancy.